Portal hypertension: at the bedside - Tow, Clara Y. (Henry Stewart Talks, 2022)
Measuring portal pressures, Pathophysiology of portal hypertension, Cirrhosis, Ascites, Hepatorenal syndrome, Varices, Hepatic encephalopathy, Complications of portal hypertension, Beta blockers